Identifikasi Kemampuan Menyimak Anak Usia Dini Melalui Video Mendongeng Digital - Siregar, Nela Hasna; Hotmauli Damanik, Meirani; Sawitri, Dewi; Trisna Mukti, Suci; Sherli Utami, Winda; Surya Amanda, Rizki (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
Listening ability is receptive oral language ability, a simple morphological and syntactic ability where individuals can retell fairy tales or stories they have just listened to. Digital storytelling is telling stories or narratives using digital technology, such as video, animation, interactive applications, or social media. In digital storytelling, stories can be enriched with multimedia elements such as images, sound, music, and special effects that are impossible in traditional storytelling. The field facts found by researchers are that the listening skills of children aged 4-6 years still appear to be quite low based on the results of initial observations. This research aims to identify the listening abilities of young children through the use of digital storytelling videos. In the current digital era, traditional learning methods are starting to shift towards being more interactive and interesting for children. This study involved 3 children aged 4-6 years from various educational backgrounds in Kindergarten at Labora Islam Mulia Kindergarten. The research method used is descriptive qualitative. Data was collected through direct observation. Direct observation involves observing children as they listen to storytelling videos presented in class. How children respond to stories verbally (e.g., asking questions or making comments) and non-verbally (e.g., facial expressions, gestures). Conduct interviews with educators regarding teachers' views about the effectiveness of using video storytelling in improving children's listening skills, observing teachers about how children's listening skills are, and including the challenges they face and the strategies children use to understand stories. The research results showed a significant increase in children's listening abilities after using digital storytelling videos. Children are better able to understand stories, identify characters, and remember storylines better. In addition, children showed higher enthusiasm in the learning process and had better attention during storytelling sessions. This research concludes that digital storytelling videos are an effective tool for improving the listening skills of young children, and recommends their use in early childhood education curricula to support the optimal development of listening skills.